HUBUNGAN KELELAHAN DAN TINGKAT STRES MAHASISWA SEMESTER AKHIR FAKULTAS Y UNIVERSITAS X DI BANYUWANGI: Relationship Between Fatigue and Stress Level in Final Students of Faculty Y University X in Banyuwangi - Khoirunisa, Arini; Dwiyanti , Endang (Journal of Community Mental Health and Public Policy, 2021)
ABSTRACTFinal semester students have a heavier study load than early-level student that can make fatigue trigger wich leads to stress. This study aimed to find out strenght relation between fatigue and stress level in the final semester students of Faculty Y University X in Banyuwangi. This study used crosssectional study and respondents were the final semester students of Faculty Y University X in Banyuwangi amounting 41 students. Data were collected through distribution of online questionnaire that fatigue level was measured by Subjective Self Rating questionnaire. While level of stress was measured by the General Health Questionnaire. The relationship strength was obtained with contingency coefficient to determine the strength of the relationship between the two variables with ordinal data category and the total population methode and the result of contingency coefficient value is 0 ,688 wich stated that there was a strong relationship between fatigue and stress levels. Most of the final semester students have moderate stress level that is 70.7%.The conclusion of the study shows there is a strong relationship between fatigue and stress level in final semester students of Faculty Y University X in Banyuwangi. It is hope that final semester students have rest time to avoid fatigue and stress.Keywords: fatigue level, stress level, final semester student ABSTRAKMahasiswa semester akhir memiliki beban belajar yang lebih berat dibandingkan mahasiswa tingkat awal yang dapat memicu kelelahan dan berujung pada timbulnya stres. Penelitian ini bertujuan untuk mengetahui kuat hubungan kelelahan dengan stres pada mahasiswa semester akhir Fakultas Y Univeritas X di Banyuwangi. Penelitian ini menggunakan studi crossectional dengan responden mahasiswa semester akhir Fakultas Y Universitas X di Banyuwangi yang berjumlah 41 mahasiswa. Data dikumpulkan melalui dengan tingkat kelelahan diukur dengan Subjective Self Rating Test. Sedangkan tingkat stres diukur dengan kuesioner General Health Questionnaire. Uji kuat hubungan dilakukan dengan contingency coefficient untuk mengetahui kuat hubungan dari dua variabel dengan kategori data ordinal serta metode total populasi dengan hasil uji diperoleh nilai koefisien kontingensi sebesar 0,688 menyatakan bahwa ada hubungan kuat antara kelelahan dengan tingkat stres. Sebagian besar mahasiswa semester akhir mengalami stres tingkat sedang yakni 70,7%. Kesimpulan dari penelitian menunjukkan hubungan kuat antara kelelahan dan tingkat stres pada mahasiswa semester akhir Fakultas Y Universitas X di Banyuwangi. Diharapkan mahasiswa semester akhir memiliki waktu istirahat agar tidak mengalami kelelahan dan stres.Kata Kunci: tingkat kelelahan, tingkat stres, mahasiswa semester akhir